Penatalaksaan Fisioterapi Pada Kasus Cervical Root Syndrome Di RSU Aisyiyah Ponorogo - Karizki, Novisa, Dwi Rosella Komala Sari SST.FT, M. Fis (2016)
Background: Cervical root syndrome is a state of irritation or suppression of spinal nerve roots in the neck area, This impingement typically produces neck and radiating arm pain or numbness, sensory deficits, or motor dysfunction in the neck and upper extremites. Objective : To find out the benefits of the use of Short Wave Diathermy ( SWD ), Transcutaneus Electrical Nerve Stimulation ( TENS ) , and therapeutic exercise in the case of cervical root syndrome. Results : After treatment for 6 times found a decrease in the degree of pain silent T0 : 4 to T6 : 2 , pain motion T0 : 7 becomes T6 : 3 , and tenderness T0 : 7 becomes T6 : 3 , an increased range of motion ( LGS ) in cervical the flexion movement T0 : 6 Cm becomes T6 : 9 cm , extensions T0 : 11 cm , lateral flexion dextra T0 : 6 Cm becomes T6 : 9 cm , lateral flexion of the left T0 : 9 cm into T6 : 9 cm , side rotation dextra T0 : 12 Cm becomes T6 : 14 cm , rotation of the left side T0 : 14 Cm becomes T6 : 14 Cm , and adannya increase functional activity of cervical T0 : 58 % to T6 : 38 % . Conclusion : after granting modalities Short wave diathermy ( SWD ) , Transcutaneus electrical nerve stimulation (TENS) , and therapeutic exercise in the case of cervical root syndrome can reduce the degree of pain , increase range of motion ( LGS ) , and enhance the functional activity of the cervical spine.